Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/ng1885
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution HLA and SNP haplotype map for disease association studies in the extended human MHC

Abstract: The proteins encoded by the classical HLA class I and class II genes in the major histocompatibility complex (MHC) are highly polymorphic and play an essential role in self/nonself immune recognition. HLA variation is a crucial determinant of transplant rejection and susceptibility to a large number of infectious and autoimmune disease1. Yet identification of causal variants is problematic due to linkage disequilibrium (LD) that extends across multiple HLA and non-HLA genes in the MHC2,3. We therefore set out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
721
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(757 citation statements)
references
References 33 publications
(38 reference statements)
21
721
2
4
Order By: Relevance
“…This makes genotyping and sequencing assays technically challenging, so genotyping has remained a low‐throughput activity, in contrast to the rest of the genome, which is amenable to more scalable technologies. Over the last several years, the compilation of large reference populations with both serological and genotyping data on MHC variation has made imputation of classical alleles possible from standard SNP array data to single amino acid resolution 48, 49. We thus now have tools to interrogate this region at scale and identify the specific functional HLA alleles driving risk.…”
Section: The Role Of the Mhcmentioning
confidence: 99%
“…This makes genotyping and sequencing assays technically challenging, so genotyping has remained a low‐throughput activity, in contrast to the rest of the genome, which is amenable to more scalable technologies. Over the last several years, the compilation of large reference populations with both serological and genotyping data on MHC variation has made imputation of classical alleles possible from standard SNP array data to single amino acid resolution 48, 49. We thus now have tools to interrogate this region at scale and identify the specific functional HLA alleles driving risk.…”
Section: The Role Of the Mhcmentioning
confidence: 99%
“…[25][26][27][28][29] Therefore, gene-disease associations in Caucasians and Chinese may be different, as has already been described in several other diseases. …”
Section: Discussionmentioning
confidence: 95%
“…As there was tight LD among the alleles of HLA and non-HLA genes in the HLA region, which extended over several mega-bases (Mb) in some haplotypes, 11,28 we have evaluated LD among these diseaseassociated alleles in the controls, DVT-negative patients and DVTpositive patients (Table 3). It was found that DPB1*0202 was not in LD with the other disease-associated alleles in both controls and Owing to the strong LD, it was difficult to determine whether IKBLp*03 or B*5201 (or both of them) was primarily associated with the disease.…”
Section: Resultsmentioning
confidence: 99%
“…19 On the other hand, earlier HLA studies in Caucasoid populations showed that some HLA alleles were associated with pulmonary arterial hypertension, but the results were not consistent with each other, [14][15][16][17][18] implying that the observed associations with HLA were specific to the investigated ethnic groups because the complexity of HLA region depends on the nature of ethnic groups. 11 It is also possible that these reports might be false-positive findings owing to the type I error in the statistical analyses, because none of the earlier studies was concerned about multiple testing. However, the possibility remains that the association with HLA might be confined to a specific category of CTEPH, because the etiology and pathogenesis of CTEPH were heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation